Pediatri Hemşirelerinin Eleştirel Düşünme Eğilim Düzeyleri ve Etkileyen Faktörler. - KOBYA BULUP, Hacer; BULUT, Elif (Turkiye Klinikleri Journal of Nursing Sciences, 2020)
Objective: The complex health conditions that disturb children today require more skills and understanding on behalf of the nurse. One of these skills and understanding is critical thinking. The aim of this study was to determine the critical thinking skill levels of pediatric nurses and the factors affecting them. Material and Methods: This descriptive study included 133 pediatric nurses working in a university and a state hospital and volunteering to participate in the study. The data were collected using the "Introductory Information Form" and "California Critical Thinking Trends Scale". Data were analyzed using SPSS (Statistical Package for Social Sciences) 23.0 package program. 95% confidence interval and significance level were used as p<0.05. Results: The pediatric nurses participating in the study have been working for 11.70±6.94 years. It was found that 66.9% of the nurses worked in the general pediatrics clinic, 93.2% participated in the internal and 36.8% outside the institution, 24.1% read scientific publications and 61.7% participated in the social activities. The mean total critical thinking trend score of the pediatric nurses participating in the study was 220.40±23.85. A statistically significant difference was found between the mean scores of critical thinking and participation in pediatric nursing institutions, participating in scientific activities, reading scientific publications and participating in social activities (p<0.05). Conclusion: The critical thinking disposition scores of the pediatric nurses were found low. Pediatric nurses' critical thinking disposition scores were low. However, participation in external scientific activities, reading scientific publications and participating in social activities were found to have a positive effect on the critical thinking disposition.